2017
DOI: 10.1002/erv.2535
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention to Ambiguous Emotional Faces in Eating Disorders: Role of Alexithymia

Abstract: Eating disorders (EDs) are often accompanied by social-emotional problems. Recently, alexithymia has been suggested to explain objective emotion processing deficits in EDs. We tested if elevated levels of alexithymia may explain emotional face-processing problems in a mixed ED group (N = 24, 19 with anorexia and five with bulimia), comparing them with high-alexithymic (N = 25) and low-alexithymic healthy controls (N = 25). Participants judged the mixture ratio of clear and ambiguous facial emotion blends while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 57 publications
(87 reference statements)
2
26
2
Order By: Relevance
“…Eye viewing itself did, however, not differ between ED females and healthy controls (Fujiwara, Kube, Rochman, Macrae-Korobkov, & Peynenburg, 2017). Reduced attention to the eye region during free face viewing was also found in a sample of women with weight-restored AN (Watson, Werling, Zucker, & Platt, 2010).…”
mentioning
confidence: 59%
“…Eye viewing itself did, however, not differ between ED females and healthy controls (Fujiwara, Kube, Rochman, Macrae-Korobkov, & Peynenburg, 2017). Reduced attention to the eye region during free face viewing was also found in a sample of women with weight-restored AN (Watson, Werling, Zucker, & Platt, 2010).…”
mentioning
confidence: 59%
“…A recent investigation using blended ambiguous expressions also found that individuals with ED had difficulties judging disgust (Fujiwara et al, ). However, in Fujiwara and colleagues' study, participants with ED experienced difficulties with more ambiguous facial expressions, whereas in this study, the ED participants exhibited worse performance in less ambiguous expressions of disgust.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study investigated the ability of a mixed sample of participants with BN and AN to judge blended emotions in facial expressions, compared with a group of healthy individuals with high alexithymia and a group with low alexithymia. Results indicated that participants with ED were less accurate judging ambiguous blends containing anger or disgust, compared with participants with low alexithymia (Fujiwara, et al, ). However, only 21% of the ED sample in this study had BN; thus, the ability to recognise emotions in ambiguous, blended facial expressions in people with BN remains largely underexplored.…”
Section: Introductions and Aimsmentioning
confidence: 95%
“…All but one study (Watson et al, 2010) reported mean age of participants (range: 14.4-44.68 years), and only four studies did not report the mean BMI or % ideal body weight (IBW) of at least one participant group (Fujiwara et al, 2017;Stefano Pallanti et al, 1998;Pinhas et al, 2014;Watson et al, 2010). All but one study (Watson et al, 2010) reported mean age of participants (range: 14.4-44.68 years), and only four studies did not report the mean BMI or % ideal body weight (IBW) of at least one participant group (Fujiwara et al, 2017;Stefano Pallanti et al, 1998;Pinhas et al, 2014;Watson et al, 2010).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…studies examined attention while viewing social stimuli. Building on this study,Fujiwara et al (2017) investigated whether differences in eye movements might drive potential difficulties in facial emotion recognition commonly found in those with EDs(Caglar-Nazali et al, 2014). Participants viewed photographs of their own and other female faces, and afterwards rated the attractiveness of parts of the faces.…”
mentioning
confidence: 99%